Soil carbon is greater under grazed paddocks than fencelines, likely due to greater dung returns - Holly M. Hay; Aaron M. Wall; Sam R. McNally; Roshean R. Woods; Louis A. Schipper (Agriculture, Ecosystems & Environment, 2026)

Integrating soil organic carbon loss into building life cycle assessment and urban planning: implications for urban sustainability practice - Gerasimos Christoforatos; Kim Pickering; Louis A. Schipper (Journal of Environmental Management, 2026)

Small methane emissions from pasture observed with eddy covariance and flux-gradient methods: are they real or artefacts? - Johannes Laubach; Aaron M. Wall; John E. Hunt; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; Louis A. Schipper (Agricultural and Forest Meteorology, 2026)

Arrhenius Activation Energy Is Not a Useful Predictor of Soil Organic Matter Transformation and Its Consequences for Global Warming - Charlotte J. Alster; Vickery L. Arcus; Louis A. Schipper (Global Change Biology, 2026)

Lowering foliage nitrogen contents reduces N2O emissions in grazed pastures: An emission factor-based modelling assessment constrained by eddy covariance measurements - Lìyǐn L. Liáng; Aaron M. Wall; Donna L. Giltrap; Miko U.F. Kirschbaum; Jordan P. Goodrich; David I. Campbell; Louis A. Schipper (Agricultural Systems, 2025)

Periodic cropping of pasture for summer-grazed turnips leads to substantial carbon loss - Aaron M. Wall; Jordan P. Goodrich; Seager Ray; David I. Campbell; Louis A. Schipper (Agricultural and Forest Meteorology, 2025)

Thermal Adaptation of Bacterial and Fungal Growth in a Geothermally Influenced Soil Transect - Charlotte J. Alster; Louis A. Schipper; Erland Bååth (Global Change Biology, 2025)
Numerous studies have investigated microbial adaptation to increasing soil temperature, but limitations in experimental design hinder comprehensive understanding. These include short‐term laboratory studies with constant environmental conditions and field studies with few distinct temperature treatments. Here, we utilized a long‐term natural soil geothermal gradient in Aotearoa, New Zealand, ranging in mean annual soil temperature (MAT) from 17°C to 42°C to explore thermal adaptation of microbial growth rates. We collected soil from 28 locations along the gradient and measured bacterial growth rate (via leucine incorporation) at eight temperatures (4°C–45°C) and fungal growth rate (via Ac‐in‐ergosterol) at two temperatures (16°C and 39°C). We then fit Macromolecular Rate Theory and the Ratkowsky equation to estimate the temperature minimum (), optimum (), and inflection point () for bacterial growth, and a temperature sensitivity index to compare relative fungal and bacterial growth rates. We found predictable changes in thermal adaptation of bacterial growth along the geothermal gradient with temperature response curves shifting 0.22°C–0.27°C per 1°C increase in MAT regardless of the temperature metric (i.e., , , and ) used. Thermal adaptation of bacterial and fungal growth increased roughly in parallel. We also compared the bacterial growth results to published temperature response data of microbial respiration (with added glucose) from this geothermal gradient. Rates of thermal adaptation for bacterial growth and microbial respiration were similar, suggesting synchronicity across microbial processes. The less than 1°C change in all measured temperatures metrics per degree increase in MAT resulted in microbial growth and activity closer to in situ temperatures at high soil temperatures and lower than in situ temperatures under non‐elevated soil temperatures. Overall, our results highlight the use of geothermal gradients and appropriate temperature models in studying thermal adaptation of soil microbial processes; the predictability of results also underscores potential for incorporating microbial thermal adaptation into soil carbon modeling efforts.

Does warming erode network stability and ecosystem multifunctionality? - Andrew D. Barnes; Julie R. Deslippe; Anton M. Potapov; Adriana L. Romero-Olivares; Louis A. Schipper; Charlotte J. Alster (Trends in Ecology & Evolution, 2024)

Effects of dairy farming management practices on carbon balances in New Zealand’s grazed grasslands: Synthesis from 68 site-years - Aaron M. Wall; Johannes Laubach; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; John E. Hunt; Paul L. Mudge; David Whitehead; Louis A. Schipper (Agriculture, Ecosystems & Environment, 2024)

Methane emissions from animal agriculture: Micrometeorological solutions for challenging measurement situations - Johannes Laubach; Thomas K. Flesch; Christof Ammann; Mei Bai; Zhiling Gao; Lutz Merbold; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; John E. Hunt; Aaron M. Wall; Louis A. Schipper (Agricultural and Forest Meteorology, 2024)

Elucidating phosphorus removal dynamics in a denitrifying woodchip bioreactor - Gimhani N. Perera; Dorisel Torres Rojas; Aldrin Rivas; Greg Barkle; Brian Moorhead; Louis A. Schipper; Rupert Craggs; Adam Hartland (Science of The Total Environment, 2024)

Atmospheric effects are stronger than soil moisture in restricting net CO2 uptake of managed grasslands in New Zealand - Jordan P. Goodrich; Aaron M. Wall; David I. Campbell; Margaret M. Barbour; Johannes Laubach; John E. Hunt; Louis A. Schipper (Agricultural and Forest Meteorology, 2024)

Flow analysis and hydraulic performance of denitrifying bioreactors under different carbon dosing treatments - Reza Moghaddam; Greg Barkle; Aldrin Rivas; Louis Schipper (Journal of Environmental Management, 2023)

Constant carbon dosing of a pilot-scale denitrifying bioreactor to improve nitrate removal from agricultural tile drainage - Reza Moghaddam; Greg Barkle; Aldrin Rivas; Dorisel Torres-Rojas; Louis Schipper (Ecological Engineering, 2023)

The carbon‐quality temperature hypothesis: Fact or artefact? - Lìyǐn L. Liáng; Miko U. F. Kirschbaum; Vickery L. Arcus; Louis A. Schipper (Global Change Biology, 2023)
Climate warming can reduce global soil carbon stocks by enhancing microbial decomposition. However, the magnitude of this loss remains uncertain because the temperature sensitivity of the decomposition of the major fraction of soil carbon, namely resistant carbon, is not fully known. It is now believed that the resistance of soil carbon mostly depends on microbial accessibility of soil carbon with physical protection being the primary control of the decomposition of protected carbon, which is insensitive to temperature changes. However, it is still unclear whether the temperature sensitivity of the decomposition of unprotected carbon, for example, carbon that is not protected by the soil mineral matrix, may depend on the chemical recalcitrance of carbon compounds. In particular, the carbon‐quality temperature (CQT) hypothesis asserts that recalcitrant low‐quality carbon is more temperature‐sensitive to decomposition than labile high‐quality carbon. If the hypothesis is correct, climate warming could amplify the loss of unprotected, but chemically recalcitrant, carbon and the resultant CO 2 release from soils to the atmosphere. Previous research has supported this hypothesis based on reported negative relationships between temperature sensitivity and carbon quality, defined as the decomposition rate at a reference temperature. Here we show that negative relationships can arise simply from the arbitrary choice of reference temperature, inherently invalidating those tests. To avoid this artefact, we defined the carbon quality of different compounds as their uncatalysed reaction rates in the absence of enzymes. Taking the uncatalysed rate as the carbon quality index, we found that the CQT hypothesis is not supported for enzyme‐catalysed reactions, which showed no relationship between carbon quality and temperature sensitivity. The lack of correlation in enzyme‐catalysed reactions implies similar temperature sensitivity for microbial decomposition of soil carbon, regardless of its quality, thereby allaying concerns of acceleration of warming‐induced decomposition of recalcitrant carbon.

Estimating the temperature optima of soil priming - Charlotte J. Alster; Allycia van de Laar; Vickery L. Arcus; Kristyn B. Numa; Aaron M. Wall; Louis A. Schipper (Soil Biology and Biochemistry, 2023)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Soil microbial sensitivity to temperature remains unchanged despite community compositional shifts along geothermal gradients - Gabriel Y. K. Moinet; Manpreet K. Dhami; John E. Hunt; Anastasija Podolyan; Liyĭn L. Liáng; Louis A. Schipper; David Whitehead; Jonathan Nuñez; Adriano Nascente; Peter Millard (Global Change Biology, 2021)
Climate warming may be exacerbated if rising temperatures stimulate losses of soil carbon to the atmosphere. The direction and magnitude of this carbon‐climate feedback are uncertain, largely due to lack of knowledge of the thermal adaptation of the physiology and composition of soil microbial communities. Here, we applied the macromolecular rate theory (MMRT) to describe the temperature response of the microbial decomposition of soil organic matter (SOM) in a natural long‐term warming experiment in a geothermally active area in New Zealand. Our objective was to test whether microbial communities adapt to long‐term warming with a shift in their composition and their temperature response that are consistent with evolutionary theory of trade‐offs between enzyme structure and function. We characterized the microbial community composition (using metabarcoding) and the temperature response of microbial decomposition of SOM (using MMRT) of soils sampled along transects of increasing distance from a geothermally active zone comprising two biomes (a shrubland and a grassland) and sampled at two depths (0–50 and 50–100 mm), such that ambient soil temperature and soil carbon concentration varied widely and independently. We found that the different environments were hosting microbial communities with distinct compositions, with thermophile and thermotolerant genera increasing in relative abundance with increasing ambient temperature. However, the ambient temperature had no detectable influence on the MMRT parameters or the relative temperature sensitivity of decomposition ( Q 10 ). MMRT parameters were, however, strongly correlated with soil carbon concentration and carbon:nitrogen ratio. Our findings suggest that, while long‐term warming selects for warm‐adapted taxa, substrate quality and quantity exert a stronger influence than temperature in selecting for distinct thermal traits. The results have major implications for our understanding of the role of soil microbial processes in the long‐term effects of climate warming on soil carbon dynamics and will help increase confidence in carbon‐climate feedback projections.

High contribution of methane in greenhouse gas emissions from a eutrophic lake: a mass balance synthesis - Arianto B. Santoso; David P. Hamilton; Louis A. Schipper; Ilia S. Ostrovsky; Chris H. Hendy (New Zealand Journal of Marine and Freshwater Research, 2021)
Lakes are ‘hotspots’ for greenhouse gas (GHG) emissions, primarily carbon dioxide (CO 2 ) and methane (CH 4 ). Understanding the processes regulating GHG emissions from lakes, and their temporal variability, is essential for more accurately quantifying the role of lakes in global GHG cycles. In this study, we identified the processes that affect CO 2 and CH 4 concentrations in a small (0.3 km 2 ) eutrophic monomictic lake (Okaro, New Zealand). A mass balance model was used to calculate changes in CO 2 and CH 4 storage in the lake as a result of internal cycling and atmospheric fluxes. To support model computations, CO 2 and CH 4 concentrations profiles were measured monthly over a one‐year period, in addition to temperature, dissolved oxygen and chlorophyll a . Annually, Lake Okaro acted as a sink of CO 2 from the atmosphere (425.4 mmol CO 2 m −2 y −1 ) and a source of CH 4 (553.4 mmol CH 4 m −2 y −1 ) equating to a net GHG emission (diffusive fluxes of CO 2 and CH 4 combined) of 0.22 kg CO 2 ‐eq m −2 y −1 . Although it may be viewed as conservative and applies only to diffusive fluxes, our study indicates that eutrophic lakes with high rates of primary production may act as a net source of GHGs.

Livestock exclusion reduces the spillover effects of pastoral agriculture on soil bacterial communities in adjacent forest fragments - Jieyun Wu; Hannah L. Buckley; Liz Curry; Bryan A. Stevenson; Louis A. Schipper; Gavin Lear (Environmental Microbiology, 2021)
Summary Forest‐to‐pasture conversion is known to cause global losses in plant and animal diversity, yet impacts of livestock management after such conversion on vital microbial communities in adjoining natural ecosystems remain poorly understood. We examined how pastoral land management practices impact soil microorganisms in adjacent native forest fragments, by comparing bacterial communities sampled along 21 transects bisecting pasture–forest boundaries. Our results revealed greater bacterial taxon richness in grazed pasture soils and the reduced dispersal of pasture‐associated taxa into adjacent forest soils when land uses were separated by a boundary fence. Relative abundance distributions of forest‐associated taxa (i.e., Proteobacteria and Nitrospirae ) and a pasture‐associated taxon (i.e., Firmicutes ) also suggest a greater impact of pastoral land uses on forest fragment soil bacterial communities when no fence is present. Bacterial community richness and composition were most related to changes in soil physicochemical variables commonly associated with agricultural fertilization, including concentrations of Olsen P, total P, total Cd, delta 15 N and the ratio of C:P and N:P. Overall, our findings demonstrate clear, and potentially detrimental effects of agricultural disturbance on bacterial communities in forest soils adjacent to pastoral land. We provide evidence that simple land management decisions, such as livestock exclusion, can mitigate the effects of agriculture on adjacent soil microbial communities.

How to measure, report and verify soil carbon change to realize the potential of soil carbon sequestration for atmospheric greenhouse gas removal - Pete Smith; Jean‐Francois Soussana; Denis Angers; Louis Schipper; Claire Chenu; Daniel P. Rasse; Niels H. Batjes; Fenny van Egmond; Stephen McNeill; Matthias Kuhnert; Cristina Arias‐Navarro; Jorgen E. Olesen; et al. (Global Change Biology, 2020)
There is growing international interest in better managing soils to increase soil organic carbon (SOC) content to contribute to climate change mitigation, to enhance resilience to climate change and to underpin food security, through initiatives such as international ‘4p1000’ initiative and the FAO's Global assessment of SOC sequestration potential (GSOCseq) programme. Since SOC content of soils cannot be easily measured, a key barrier to implementing programmes to increase SOC at large scale, is the need for credible and reliable measurement/monitoring, reporting and verification (MRV) platforms, both for national reporting and for emissions trading. Without such platforms, investments could be considered risky. In this paper, we review methods and challenges of measuring SOC change directly in soils, before examining some recent novel developments that show promise for quantifying SOC. We describe how repeat soil surveys are used to estimate changes in SOC over time, and how long‐term experiments and space‐for‐time substitution sites can serve as sources of knowledge and can be used to test models, and as potential benchmark sites in global frameworks to estimate SOC change. We briefly consider models that can be used to simulate and project change in SOC and examine the MRV platforms for SOC change already in use in various countries/regions. In the final section, we bring together the various components described in this review, to describe a new vision for a global framework for MRV of SOC change, to support national and international initiatives seeking to effect change in the way we manage our soils.

Sedimentary Environment Influences Ecosystem Response to Nutrient Enrichment - Emily J. Douglas; Conrad A. Pilditch; Andrew M. Lohrer; Candida Savage; Louis A. Schipper; Simon F. Thrush (Estuaries and Coasts, 2018)

Macromolecular rate theory ( MMRT ) provides a thermodynamics rationale to underpin the convergent temperature response in plant leaf respiration - Liyin L. Liang; Vickery L. Arcus; Mary A. Heskel; Odhran S. O'Sullivan; Lasantha K. Weerasinghe; Danielle Creek; John J. G. Egerton; Mark G. Tjoelker; Owen K. Atkin; Louis A. Schipper (Global Change Biology, 2018)
Temperature is a crucial factor in determining the rates of ecosystem processes, for example, leaf respiration ( R ) – the flux of plant respired CO 2 from leaves to the atmosphere. Generally, R increases exponentially with temperature and formulations such as the Arrhenius equation are widely used in earth system models. However, experimental observations have shown a consequential and consistent departure from an exponential increase in R . What are the principles that underlie these observed patterns? Here, we demonstrate that macromolecular rate theory ( MMRT ), based on transition state theory (TST) for enzyme‐catalyzed kinetics, provides a thermodynamic explanation for the observed departure and the convergent temperature response of R using a global database. Three meaningful parameters emerge from MMRT analysis: the temperature at which the rate of respiration would theoretically reach a maximum (the optimum temperature, T opt ), the temperature at which the respiration rate is most sensitive to changes in temperature (the inflection temperature, T inf ) and the overall curvature of the log(rate) versus temperature plot (the change in heat capacity for the system, ). On average, the highest potential enzyme‐catalyzed rates of respiratory enzymes for R are predicted to occur at 67.0 ± 1.2°C and the maximum temperature sensitivity at 41.4 ± 0.7°C from MMRT . The average curvature (average negative ) was −1.2 ± 0.1 kJ mol −1 K −1 . Interestingly, T opt , T inf and appear insignificantly different across biomes and plant functional types, suggesting that thermal response of respiratory enzymes in leaves could be conserved. The derived parameters from MMRT can serve as thermal traits for plant leaves that represent the collective temperature response of metabolic respiratory enzymes and could be useful to understand regulations of R under a warmer climate. MMRT extends the classic TST to enzyme‐catalyzed reactions and provides an accurate and mechanistic model for the short‐term temperature response of R around the globe.

Deforestation may increase soil carbon but it is unlikely to be continuous or unlimited - Louis Schipper; Pete Smith (Global Change Biology, 2018)

Macrofaunal Functional Diversity Provides Resilience to Nutrient Enrichment in Coastal Sediments - Emily J. Douglas; Conrad A. Pilditch; Casper Kraan; Louis A. Schipper; Andrew M. Lohrer; Simon F. Thrush (Ecosystems, 2017)

Carbon dioxide emissions and sediment organic carbon burials across a gradient of trophic state in eleven New Zealand lakes - Arianto B. Santoso; David P. Hamilton; Chris H. Hendy; Louis A. Schipper (Hydrobiologia, 2017)

Herbicide application during pasture renewal initially increases root turnover and carbon input to soil in perennial ryegrass and white clover pasture - Samuel R. McNally; Daniel C. Laughlin; Susanna Rutledge; Mike B. Dodd; Johan Six; Louis A. Schipper (Plant and Soil, 2017)

Irrigating grazed pasture decreases soil carbon and nitrogen stocks - Paul L. Mudge; Francis M. Kelliher; Trevor L. Knight; Denis O'Connell; Scott Fraser; Louis A. Schipper (Global Change Biology, 2017)
The sustainability of using irrigation to produce food depends not only on the availability of sufficient water, but also on the soil's ‘response’ to irrigation. Stocks of carbon (C) and nitrogen (N) are key components of soil organic matter ( SOM ), which is important for sustainable agricultural production. While there is some information about the effects of irrigation on soil C stocks in cropping systems, there is a paucity of such studies in pastoral food production systems. For this study, we sampled soils from 34 paired, irrigated and unirrigated pasture sites across New Zealand ( NZ ) and analysed these for total C and N. On average, irrigated pastures had significantly ( P 0.05) less soil carbon (C) and nitrogen (N) than adjacent unirrigated pastures, with differences of 6.99 t C ha −1 and 0.58 t N ha −1 in the uppermost 0.3 m. Differences in C and N tended to occur throughout the soil profile, so the cumulative differences increased with depth, and the proportion of the soil C lost from deeper horizons was large. There were no relationships between differences in soil C and N stocks and the length of time under irrigation. This study suggests SOM will decrease when pastures under a temperate climate are irrigated. On this basis, increasing the area of temperate pasture land under irrigation would result in more CO 2 in the atmosphere and may directly and indirectly increase N leaching to groundwater. Given the large and increasing area of land being irrigated both in NZ and on a global scale, there is an urgent need to determine whether the results found in this study are also applicable in other regions and under different land management systems (e.g. arable).

Root carbon inputs under moderately diverse sward and conventional ryegrass-clover pasture: implications for soil carbon sequestration - Samuel Rae McNally; Daniel C. Laughlin; Susanna Rutledge; Mike B. Dodd; Johan Six; Louis A. Schipper (Plant and Soil, 2015)

Thermodynamic theory explains the temperature optima of soil microbial processes and high Q 10 values at low temperatures - Louis A. Schipper; Joanne K. Hobbs; Susanna Rutledge; Vickery L. Arcus (Global Change Biology, 2014)
Our current understanding of the temperature response of biological processes in soil is based on the Arrhenius equation. This predicts an exponential increase in rate as temperature rises, whereas in the laboratory and in the field, there is always a clearly identifiable temperature optimum for all microbial processes. In the laboratory, this has been explained by denaturation of enzymes at higher temperatures, and in the field, the availability of substrates and water is often cited as critical factors. Recently, we have shown that temperature optima for enzymes and microbial growth occur in the absence of denaturation and that this is a consequence of the unusual heat capacity changes associated with enzymes. We have called this macromolecular rate theory – MMRT (Hobbs et al ., , ACS Chem. Biol. 8:2388). Here, we apply MMRT to a wide range of literature data on the response of soil microbial processes to temperature with a focus on respiration but also including different soil enzyme activities, nitrogen and methane cycling. Our theory agrees closely with a wide range of experimental data and predicts temperature optima for these microbial processes. MMRT also predicted high relative temperature sensitivity (as assessed by Q 10 calculations) at low temperatures and that Q 10 declined as temperature increases in agreement with data synthesis from the literature. Declining Q 10 and temperature optima in soils are coherently explained by MMRT which is based on thermodynamics and heat capacity changes for enzyme‐catalysed rates. MMRT also provides a new perspective, and makes new predictions, regarding the absolute temperature sensitivity of ecosystems – a fundamental component of models for climate change.

Denitrification Potential in Lake Sediment Increases Across a Gradient of Catchment Agriculture - Denise A. Bruesewitz; David P. Hamilton; Louis A. Schipper (Ecosystems, 2011)

Photodegradation leads to increased carbon dioxide losses from terrestrial organic matter - SUSANNA RUTLEDGE; DAVID I. CAMPBELL; DENNIS BALDOCCHI; LOUIS A. SCHIPPER (Global Change Biology, 2010)
CO 2 production in terrestrial ecosystems is generally assumed to be solely biologically driven while the role of abiotic processes has been largely overlooked. In addition to microbial decomposition, photodegradation – the direct breakdown of organic matter (OM) by solar irradiance – has been found to contribute to litter mass loss in dry ecosystems. Previous small‐scale studies have shown that litter degradation by irradiance is accompanied by emissions of CO 2 . However, the contribution of photodegradation to total CO 2 losses at ecosystems scales is unknown. This study determined the proportion of the total CO 2 losses caused by photodegradation in two ecosystems: a bare peatland in New Zealand and a seasonally dry grassland in California. The direct effect of solar irradiance on CO 2 production was examined by comparing daytime CO 2 fluxes measured using eddy covariance (EC) systems with simultaneous measurements made using an opaque chamber and the soil CO 2 gradient technique, and with night‐time EC measurements under the same soil temperature and moisture conditions. In addition, a transparent chamber was used to directly measure CO 2 fluxes from OM caused by solar irradiance. Photodegradation contributed 19% of the annual CO 2 flux from the peatland and almost 60% of the dry season CO 2 flux from the grassland, and up to 62% and 92% of the summer mid‐day CO 2 fluxes, respectively. Our results suggest that photodegradation may be important in a wide range of ecosystems with exposed OM. Furthermore, the practice of partitioning daytime ecosystem CO 2 exchange into its gross components by assuming that total daytime CO 2 losses can be approximated using estimates of biological respiration alone may be in error. To obtain robust estimates of global ecosystem–atmosphere carbon transfers, the contribution of photodegradation to OM decomposition must be quantified for other ecosystems and the results incorporated into coupled carbon–climate models.

Foliar 15N natural abundance indicates phosphorus limitation of bog species - Beverley R. Clarkson; Louis A. Schipper; Bernard Moyersoen; Warwick B. Silvester (Oecologia, 2005)

Carbon exchange of grazed pasture on a drained peat soil - Joost P. Nieveen; David I. Campbell; Louis A. Schipper; Ian J. Blair (Global Change Biology, 2005)
Land‐use changes have contributed to increased atmospheric CO 2 concentrations. Conversion from natural peatlands to agricultural land has led to widespread subsidence of the peat surface caused by soil compaction and mineralization. To study the net ecosystem exchange of carbon (C) and the contribution of respiration to peat subsidence, eddy covariance measurements were made over pasture on a well‐developed, drained peat soil from 22 May 2002 to 21 May 2003. The depth to the water table fluctuated between 0.02 m in winter 2002 to 0.75 m during late summer and early autumn 2003. Peat soil moisture content varied between 0.6 and 0.7 m 3 m −3 until the water table dropped below 0.5 m, when moisture content reached 0.38 m 3 m −3 . Neither depth to water table nor soil moisture was found to have an effect on the rate of night‐time respiration (ranging from 0.4–8.0 μmol CO 2 m −2 s −1 in winter and summer, respectively). Most of the variance in night‐time respiration was explained by changes in the 0.1 m soil temperature ( r 2 =0.93). The highest values for daytime net ecosystem exchange were measured in September 2002, with a maximum of −17.2 μmol CO 2 m −2 s −1 . Grazing events and soil moisture deficiencies during a short period in summer reduced net CO 2 exchange. To establish an annual C balance for this ecosystem, non‐linear regression was used to model missing data. Annually integrated (CO 2 ) C exchange for this peat–pasture ecosystem was 45±500 kg C ha −1 yr −1 . After including other C exchanges (methane emissions from cows and production of milk), the net annual C loss was 1061±500 kg C ha −1 yr −1 .

Vegetation and peat characteristics of restiad bogs on Chatham Island (Rekohu), New Zealand - Beverley R. Clarkson; Louis A. Schipper; Bruce D. Clarkson (New Zealand Journal of Botany, 2004)
Restiad bogs dominated by Sporadanthus traversii on Chatham Island, New Zealand, were sampled to correlate vegetation patterns and peat properties, and to compare with restiad systems dominated by Sporadanthus ferrugineus and Empodisma minus in the Waikato region, North Island, New Zealand. Classification and ordination resulted in five groups that reflected a disturbance gradient. The largest S. traversii group, which comprised plots from central, relatively intact bogs, had the lowest levels of total nitrogen (mean 1.20 mg cm ‐3 ), total phosphorus (mean 0.057 mg cm ‐3 ), total potassium (mean 0.083 mg cm ‐3 ), and available phosphorus (mean 18.6 (Ag cm ‐3 ). Modification by drainage, stock, and fires resulted in a decline of S. traversii and an increase of Gleichenia dicarpa fern cover, together with elevated peat nutrient levels and higher bulk density. Compared with peat dominated by Sporadanthus ferrugineus or Empodisma minus in relatively unmodified Waikato restiad bogs, Chatham Island peat under S. traversii has significantly higher total potassium, total nitrogen, available phosphorus, bulk density, and von Post decomposition indices, and significantly lower pH. Sporadanthus traversii and Empodisma minus have similar ecological roles in restiad bog development, occupying a relatively wide nutrient range, and regenerating readily from seed after fire. Despite differences in root morphology, S. traversii and E. minus are the major peat formers in raised restiad bogs on Chatham Island and in Waikato, respectively, and could be regarded as ecological equivalents.

Vegetation and peat characteristics in the development of lowland restiad peat bogs, North Island, New Zealand - Beverley R. Clarkson; Louis A. Schipper; Anthony Lehmann (Wetlands, 2004)